'Hurricane' Debbie – 60 years on: a fresh analysis. (8th August 2021) - Graham, Edward; Smart, David
Abstract : Major windstorms are a recurring characteristic of the Irish climate. Here, in a fresh analysis of the events of 16 September 1961 made using hourly SYNOP data and hitherto undiscovered SHIP reports, we confirm that Debbie was an extremely severe extratropical windstorm and that a new Irish mean windspeed record of 76kn (87mph) may have been set at Malin Head meteorological station.